VeggieTales. Beauty and the beet [videorecording (DVD)] (Big Idea, 2014)
Mirabelle and her traveling family band are determined to make their next gig at Vegetable Square Garden. On their journey, a winter storm hits, and they get stuck at a run-down resort. Mr. Beet, the grumpy manager makes them sing and clean for their supper. Why is Mr. Beet such a beast? And can Mirabelle's kindness change him? Find out in the hilarious and heartwarming tale of unconditional love.